Postgraduates supervisor preferences among PHD students using Analytical Hierarchy Process - Nur Hanisah Amirah , Ab Rahman (2014)
This survey was conducted to identify the criteria in selecting supervisor in University Malaysia Pahang. Besides that, the objective of this study was to identify the factors affecting the selection and to rank the most importance factors in selecting the supervisor also Survey on the postgraduate students with use the AHP analysis in evaluating their criteria to become a supervisor of the project using AHP. Sets of questionnaire were developed and data was collected by hand-distributed. Total sample of 140 respondents was used in this study. The result of this study showed that, for the ﬁrst criterion which is qualiﬁcation, the factor of the higher affect the selection. For the second higher after qualiﬁcation is experience criterion. The factor of knowledge is the third factor higher after the second. For the last factor was the commitment that the factor doesn’t affect the selection. After compare and rank all the criteria, supervisor relationship which is criterion number one become the most importance criteria that affect the supervisor selection in University Malaysia Pahang